Evaluation of Antioxidant Polyphenols from Selected Mangrove Plants of India - AGORAMOORTHY, GOVINDASAMY; CHEN, FU-AN; VENKATESALU, VENUGOPALAN; KUO, DAIH-HUANG; SHEA, PO-CHUEN (Asian Journal of Chemistry, 2010)
Mangroves and halophytes are a unique group of vascular plants that occur in saline coastal habitats. Some mangroves and halophytes are used for a wide range of conditions including bacterial, fungal and viral diseases. These specialized plants are known to tolerate extreme environmental conditions. However, little is known on the antioxidant potentials of India's mangroves and halophytes. We have evaluated 5 halophytic plants (Arthrocnemum indicum, Suaeda monoica, S. maritima, Sesuvium portulacastrum and Ipomoea pes-caprae) and 8 mangrove plants (Avicennia officinalis, Bruguiera cylindrica, Ceriops decandra, Rhizophora apiculata, R. mucronata, Aegiceras corniculatum, Excoecaria agallocha and Acanthus ilicifolius) collected from Tamil Nadu (India) to determine total polyphenol content and antioxidant activity (by 2,2-diphenyl-1,1-picrylhydrazyl DPPH free radical scavenging assay against α-tocopherol). The total polyphenol content ranged from 23.5 to 384.2 mg/g dry weight and the highest free radical scavenging activity was found in E. agallocha (30.3 μg/mL). Moreover, higher DPPH radical scavenging activity was also found in species such as B. cylindrica (42.9 μg/mL), C. decandra (51.9 μg/mL), R. apiculata (64.9 μg/mL), A. corniculatum (74.3 μg/mL), R. mucronata (79.7 μg/ mL) and I. pes-caprae (83.7 μg/mL), respectively. Between mangroves and halophytes, the polyphenols was significantly higher among 8 mangrove species than that of 5 salt marsh halophytes. Our research indicates that India's mangrove plants have the potential in scavenging free radicals and can be a vital source of antioxidant phytochemicals.